Launching: The experiences of two young adults with intellectual disability and their families in transition to individual supported living - Isaacson, Naomi; Cocks, Errol; Netto, Julie Ann (Taylor & Francis, 2014)
Background: A major milestone in the transition to adulthood is leaving the parental home, known as launching. This study explored the experiences of 2 young people with intellectual disability during launching into individual supported living, including the impact of a Western Australian (WA) funding approach. Method Two case studies employed interviews, documentation review, and observations. Three staff members of the WA Disability Services Commission participated Results: The transition period was stressful for parents. Gaining independence occurred gradually for the young adults and was influenced by parent involvement. All parents desired more formal support. Social isolation was a major issue for the young adults. Conclusions Families need long-term assistance to prepare for launching, and parents may need reassurance as they withdraw from their caring role. More consideration is needed into how young people with intellectual disability may be best supported to develop friendships.